Besedje stare kmečke delovne šege na Koroškem – steljeraje - Benko, Anja (Slavia Centralis, 2020)
The Lexis of an Old Farming Procedure, Steljeraja, in Carinthia The article presents the lexis of an old Carinthian working custom steljeraja in the form of a dialect dictionary. The lexis is based on a film on DVD made by the locals on the Golak’s farm in Dolgo Brdo near the town of Prevalje na Koroškem in 2007. The aim of the article is to juxtapose and compare the two Carinthian dialects based on the old farming procedure steljeraja, namely, (1) the Carinthian Mežica dialect (koroško-mežiško) and (2) the Carinthian Podjuna dialect (koroško-podjunsko).